Left atrial function in male veteran endurance athletes with paroxysmal atrial fibrillation - Sørensen, Eivind; Myrstad, Marius; Solberg, Magnar Gangås; Øie, Erik; Tveit, Arnljot; Aarønæs, Marit (European heart journal cardiovascular imaging, 2021)
Abstract Aims To assess left atrial (LA) function in sinus rhythm in veteran athletes with a history of paroxysmal atrial fibrillation (AF) exposed to prolonged endurance exercise compared with veteran athletes without AF and controls with and without paroxysmal AF from a non-athletic population. Methods and results Three hundred and two male participants from four groups, veteran recreational skiers with paroxysmal AF (n = 62), veteran skiers without AF (n = 89), and controls from a non-athletic population with (n = 62) and without paroxysmal AF (n = 89) underwent an echocardiographic examination in sinus rhythm to evaluate LA anatomy and function. The skiers (mean age 70.8±6.7 years) reported an average exposure to regular endurance exercise for 40–50 years. LA maximum and minimum volumes were larger in skiers (P < 0.001). LA volumes differed within the athletic and non-athletic groups with larger volumes in the AF groups ( P < 0.001). We observed a considerable overlap in LA volumes among non-athletes with AF and athletes without AF. LA reservoir strain (33.6% ± 4.8% vs. 28.3% ± 6.7% P < 0.001) and contractile strain (18.3% ± 4.0% vs. 15.0% ± 5.2% P < 0.001) were lower in both AF groups regardless of athletic status. LA reservoir strain was superior to volumetric measurements at identifying participants with AF (area under the curve 0.740 ±0.041). Conclusion Male veteran athletes had significantly larger LA volumes than non-athletes. In contrast, LA strain values were similar in athletes and non-athletes with paroxysmal AF, and significantly lower than in subjects without AF. Graphical Abstract